Management software for pedigree and production of New World Camelids: Pacokipu and Llamakipu - Cruz, Alan (2021)
Genealogical and productive records are the most important pillars within genetic and genomic improvement programs, where the diversity of data that can be collected must be systematized and related, to carry out an adequate statistical analysis considering all the factors that influence the variables. On the other hand, the current proposals do not contemplate the total registration of the population, both genealogical and productive records. Moreover, there is no software that allows systematizing, ordering and providing objective and measurable information in an orderly manner within the management of domestic camelids. For this reason, the construction of a computer application was proposed allowing the collection of genealogical and productive records of the entire population of both alpacas and llamas within the herds. As a result, the computer application called "Pacokipu" and "Llamakipu" was developed for alpacas and llamas, respectively, and were based on Microsoft Access, with two programming languages, the first with Microsoft Access Macros and Visual Basic for Applications (VBA) and the second with Structured Query Language (SQL). The application uses three elements where it stores and orders the information of the records in 23 tables, 29 queries and 93 forms. The design of the computer application allows a friendly management of any domestic camelid production center, becoming a tool for the management and administration of the animals within the herd and at the same time as a software to systematize the information collected from both genealogical and productive records, to be used within the genetic and genomic improvement programs in alpacas and llamas.